2016
DOI: 10.1038/nature19843
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale thermal imaging of dissipation in quantum systems

Abstract: Energy dissipation is a fundamental process governing the dynamics of physical, chemical, and biological systems. It is also one of the main characteristics distinguishing quantum and classical phenomena. In condensed matter physics, in particular, scattering mechanisms, loss of quantum information, or breakdown of topological protection are deeply rooted in the intricate details of how and where the dissipation occurs. Despite its vital importance the microscopic behavior of a system is usually not formulated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
175
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 55 publications
4
175
0
Order By: Relevance
“…Since the thickness of the graphene/hBN system is about 50 nm, which corresponds to about 150 atomic layers, this value of Z is physically reasonable. We also note that LS ≈ −22 meV agrees with the energy of a defect formed by a hydrogen adatom [18]. This highlights the use of resonance cooling as a way to identify the nature of a defect.…”
Section: Comparison To Experimentssupporting
confidence: 61%
See 2 more Smart Citations
“…Since the thickness of the graphene/hBN system is about 50 nm, which corresponds to about 150 atomic layers, this value of Z is physically reasonable. We also note that LS ≈ −22 meV agrees with the energy of a defect formed by a hydrogen adatom [18]. This highlights the use of resonance cooling as a way to identify the nature of a defect.…”
Section: Comparison To Experimentssupporting
confidence: 61%
“…Recently impurity-assisted electron-lattice cooling in graphene was imaged using the nanoscale thermometry scanning probe technique [18,19]. It was found that the dominant contribution to cooling arises from resonant scatterers with the energies of the resonances positioned near the Dirac point.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, conceivably, the annihilation of Abrikosov's V-AV pairs can be detected by measuring the magnetization response of the sample as a function of time, what would require fast and sensitive detection scheme. Another interesting aspect is that the local increase of the temperature in the annihilation is of the order of 10 −3 T c , which can be measured by a SQUID thermal sensor as described by Halbertal et al [58].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since W ψ is due to the relaxation of ψ, a narrower region is dominated by this dissipation mechanism. Recently, Halbertal and coworkers have shown to be possible imaging thermal dissipation in nanoscopic systems by using nanoSQUIDs [58]. Then, our theoretical approach should be experimentally confirmed since ∆T is of the order of 10…”
Section: Heat Diffusionmentioning
confidence: 99%